Participatory Mapping of Mid-Holocene Anthropogenic Landscapes in Guyana with Kite Aerial Photography (Global Journal of Human-Social Science, 2020)
The nature and degree of human modifications of humid tropical forests in Amazonia have been widely debated over the past two decades. Many regions provide significant evidence of late Holocene anthropogenic influence by settled populations, but the antiquity of human interventions is still poorly understood due to a lack of earlier archaeological sites across the broad region, particularly pertaining to the mid-Holocene. Here we report on Amerindian occupations spanning the period from ca. 6000-3000 BP along the middle Berbice River, Guyana, including early evidence in Amazonia of cultural practices widely considered indicative of settled villages, notably terra preta or "black earth" soils, mound construction, and ceramic technology. These more settled occupations of the mid-Holocene initiated a trajectory of landscape domestication extending into historical times, including larger-scale late Holocene social formations. Collaborative research with local indigenous communities, including archaeological excavations, landscape mapping using kite based aerial photography, and three-dimensional photogrammetry, was designed to promote the decolonization of archaeological knowledge production and encourage indigenous ownership of Amerindian history and cultural heritage in Guyana.
Keywords: amazonia; archaeology; mid-holocene; human-natural systems; indigenous peoples